Literature Review: Peran Ibu dalam Keberhasilan Pemberian ASI Eksklusif - Yenny Rahmawati; Hapsari Windayanti; Indriyani Suroso; Kurniawati; Amilatun Azizah; Sairoh; Tri Fitriana Sakti (Universitas Ngudi Waluyo, 2024)
The World Health Organization Who (2019) recommends to mothers around the world to breastfeed their babies exclusively for the first 6 (six) months after the baby is born to achieve optimal growth, development and health. This recommendation has been followed by various countries in the world, one of which is Indonesia. UNICEF (United Nations International Children's Emergency Fund) states that 30 thousand deaths of children under five in Indonesia and 10 million deaths of children under five worldwide every year can be prevented through exclusive breastfeeding for 6 months from the first after the birth of the baby without giving additional food and drinks to the baby. The Indonesian government realizes the importance of infants' right to exclusive breastfeeding and its impact by issuing a series of restrictions. The provisions of Government Regulation No. 33 of 2012 clearly stipulate that